Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Transparansi Pengungkapan Sukarela - Muhammad Azka Abdurrahman; Nuramalia Hasanah; Tuty Sariwulan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study analyze the effect of financial conditions and company size on the transparency of voluntary disclosure in financial statements. The financial conditions in this research are profitability and leverage, while company size is measured using the company's total assets. The analytical technique used is multiple linear regression analysis, processed using IBM SPSS Statistics 23. The population in this study consists of transportation companies listed on the Indonesia Stock Exchange from 2019 to 2022, selected using purposive sampling, resulting in a total of 84 data points over four years. The results of this study indicate that profitability and leverage influence voluntary disclosure, whereas company size does not affect voluntary disclosure.